(679) هياكل الأنظمة الدولية للحسابات القومية والجداول الموجهة - سيد أحمد البواب (معهد التخطيط القومى, 2026)
ملخص تستعرض هذه المذكرة البحثية الصادرة عن معهد التخطيط القومي في أغسطس ١٩٦٦ الهياكل التفصيلية لأنظمة الحسابات القومية الدولية، متمثلة في نظام هيئة الأمم المتحدة ونظام منظمة التعاون الاقتصادي الأوروبي، وذلك بهدف توفير مرجع علمي شامل باللغة العربية يشرح المفاهيم الأساسية اللازمة لوصف وتحليل النظم الاقتصادية للدول. وتوضح الدراسة الأسس المحاسبية التي تعتمد على تقسيم الاقتصاد إلى قطاعات تنظيمية رئيسية تشمل قطاعات الأعمال والعائلات والحكومة، وربطها بحسابات النشاط الاقتصادي المتمثلة في حسابات الإنتاج والتخصيص والعمليات الرأسمالية والحساب الخارجي، مما يسمح بتتبع التيارات المالية والمادية وتحديد المجاميع الكبرى مثل الناتج المحلي الإجمالي والدخل القومي وفق معايير دولية موحدة تضمن دقة المقارنات والتحليلات الاقتصادية التنموية. كما يتضمن الملف عرضاً للجداول الموحدة والمساعدة التي تربط الحسابات ببعضها وتسمح بعرض أكثر تفصيلاً لتوزيع الدخل وتمويل تكوين رأس المال والعمليات الخارجية، مع شرح كيفية اشتقاق كل حساب ليتصل بواحد من المجاميع الاقتصادية المألوفة. وتهدف المذكرة من خلال هذا العرض التفصيلي إلى تمكين الباحثين والمخططين من فهم قواعد المحاسبة القومية وتطبيقها عملياً، مع إمكانية إجراء التعديلات التي تقتضيها الظروف المحلية، مؤكدة أن هذه الأنظمة تمثل الركيزة الأساسية لوضع الخطط القومية ومتابعة أداء القطاعات المختلفة بما يخدم أهداف التنمية الاقتصادية والاجتماعية الشاملة This research paper, issued by the National Planning Institute in August 1966, reviews the detailed structures of international national accounts systems, namely the United Nations system and the OECD system. Its aim is to provide a comprehensive scientific reference in Arabic that explains the fundamental concepts necessary for describing and analyzing national economic systems. The study clarifies the accounting principles that rely on dividing the economy into major organizational sectors, including businesses, households, and government, and linking these to economic activity accounts such as production, allocation, capital transactions, and the external account. This allows for tracking financial and material flows and determining major aggregates, such as GDP and NIG, according to unified international standards that ensure the accuracy of comparisons and developmental economic analyses . The document also includes a presentation of the standardized and auxiliary tables that link the accounts together and allow for a more detailed view of income distribution, capital formation financing, and external operations, explaining how each account is derived to relate to one of the familiar economic aggregates. Through this detailed presentation, the memorandum aims to enable researchers and planners to understand and practically apply the rules of national accounting, with the possibility of making adjustments as required by local circumstances. It emphasizes that these systems represent the cornerstone for developing national plans and monitoring the performance of various sectors in a way that serves the goals of comprehensive economic and social development .